Life above the clouds : philosophy in the films of Terrence Malick - DeLay, Steven, 1986- (Albany : SUNY Press, 2023)
The definitive philosophical exploration of the work of pioneering filmmaker Terrence Malick.
Malickian Cinema at the Intersection of Art and Philosophy An Introduction -- Part I. Cinematic Experience as Ethical Reflection and Spiritual Exercise -- Part II. Mystery, Evil, Creation: Framing the "Big Questions" -- Part III. Explorations of Image and Voiceover -- Part IV. The Pursuit of Freedom and Transcendence
Includes bibliographical references, filmography, and index.
Includes bibliographical references and index.
Online resource title from digital title page; (viewed on March 6, 2023)
eBooks on EBSCOhost
Keywords: Malick, Terrence, -- 1943- -- Criticism and interpretation; Malick, Terrence, -- 1943- -- Philosophy; Malick, Terrence, -- 1943-; Philosophy in motion pictures; Philosophie au cinéma.; PERFORMING ARTS / Film & Video / History & Criticism; Philosophy; Philosophy in motion pictures; Electronic books; Criticism, interpretation, etc